MRI findings in children with migraine or tension-type headache - Rabia Tütüncü Toker; Ilknur Ozdeniz Mutlucan; Cigdem Tanrıverdi; Aylin Bican Demir (BMC, 2023)
Abstract Purpose Migraine and tension-type headache are common primary headaches in children. There is a risk of developing secondary headache in children. The current study was aimed to evaluate magnetic resonance imaging findings (MRI) in children with migraine or tension-type headache. Methods The study was planned in children with migraine or tension-type headaches who have been followed up in the pediatric neurology outpatient clinic with regular office visits for at least two years and had neuroimaging in the last year. Results 280 patients (187 female patients) datas were studied. 91 (61 female patients) were followed up with the diagnosis of migraine and 189 (126 female patients) with the diagnosis of tension-type headaches. The age of patients was found to be 13.1 ± 3.4 years. Brain tumor was found in one child with tension-type headache who had papilledema. Incidental MRI findings found 7.7% and 12.7% in migraine and tension-type headache, respectively. MRI findings in the study were arachnoid cyst (14), pituitary adenoma (6), mega cisterna magna (6), pineal cyst (3), non-specific gliosis (2) and tumor (1). Conclusion Arachnoid cysts were found incidental as the most common MRI finding in children with migraine or tension-type headache. The rare life-threatening secondary headache may develop in children. The fundus examination as a complement to the neurological examination can be useful for requesting MRI.